Nature-based approaches for increasing the use of solar energy in future power systems - Ustun, Taha Selim (Frontiers in Future Transportation, 2024)
One solution is inspired by nature, such as the behavior of bees, butterflies, or ants. When properly applied, the natural behavior of animals can help optimize the interaction between different renewable energy-based generators and create a more stable microgrid. There are several approaches to stabilizing such systems using novel optimization techniques. Some optimize the relationship between generators using rotating machines and inverters. The penetration of renewable generation is about increasing the share of inverter-connected generators in the system without causing stability problems. Because renewable resources are intermittent and non-dispatchable, it is vital to create a diverse portfolio where the overall system achieves some stability. For example, if a local grid is served by photovoltaic (PV) panels, wind generation, and a small hydro plant, the variable nature of these resources can complement each other. On a sunny day, the PV output might be very high, and the wind might not be as significant. Conversely, on a rainy day, clouds can reduce PV output while precipitation can feed the local hydroelectric plant. Similarly, on a windy day, wind generation could supplement other generations. While the idea is qualitatively understandable, finding the right balance is not trivial. Moreover, many factors at play change independently and affect the outcome. The available renewable energy resources, their profiles, and the local load conditions vary from site to site. Optimizing these systems at the planning, operation, and control levels requires a systematic approach. Nature-inspired optimization algorithms have an advantage in doing just that.